Transformasi Borobudur Marathon: Dari Ajang Lari Menuju Magnet Wisata Olahraga Jawa Tengah - Pranoto Pranoto; Sukrisno Sukrisno; Srinata Dwijaningtyas (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2023)
This qualitative study examines the development of tourist interest in the Borobudur Marathon as a sports tourism destination in Central Java from 1990 to 2022. Through analysis of participant data and successful implementation, the study shows a significant transformation from a simple running race to a world-class sports tourism event that has a significant economic impact with an estimated turnover of IDR 10 billion in 2022. The results of the study indicate that the friendliness of the local community, sustainable innovation, and integration with MSMEs are the main keys to the growth of tourist interest. By using a qualitative approach and descriptive analysis, this study contributes to the understanding of the development of sport tourism in Indonesia, especially in the context of utilizing cultural heritage as the main attraction.